"Several birds with one stone" strategy of pH/thermoresponsive flame-retardant/photothermal bactericidal oil-absorbing material for recovering complex spilled oil. (20th November 2022) - Chen, Ya; Lin, Jing; Mersal, Gaber A.M.; Zuo, Jianliang; Li, Jialin; Wang, Qiying; Feng, Yuhong; Liu, Jianwei; Liu, Zili; Wang, Bin; Xu, Ben Bin; Guo, Zhanhu
Abstract : An ingenious design strategy of oil-absorbing foam is proposed to deal with thorny issue on complex spilled oil or harsh oil-recycling operating conditions. A pH/thermoresponsive flame-retardant/photothermal bactericidal P-Fe3 O4 -PDA@MF oil-absorbing foam is developed. Oil-absorbing foam is featured with "Several birds with one stone" functions of maneuverable magnetic recovery of spilled crude oil, complex oily waste, fire risk management. Oil-absorbing foam demonstrates with superior performance in recovery efficiency of spilled oil, autodesorption of crude oil, and autorecycling of oil-absorbing material. Abstract: Although many material designs or strategic methods have been proposed for treating oil spills and oily wastewater, the complex oily state, dealing with the harsh operating conditions of oil–water separation (such as the recovery of viscous spilled crude oil, bacteria-containing oily wastewater, and removal of spilled oil under fire), and the autorecycling of oil and absorption materials remain a great challenge. This work proposed an ingenious design strategy of "several birds with one stone" to prepare pH/thermoresponsive flame-retardant/photothermal bactericidal P-Fe3 O4 -polydopamine (PDA)@melamine–formaldehyde (MF) foams. This design makes the foams remarkably effective in the recovery of spilled viscous crude oil as well as in the separation of bacteria-containing oily emulsions, particularly for instant fire extinguishing by magnetically controlled oil absorption as well as for fire alarms. The photothermal effect and pH response induce a change in the surface wettability of the foams, facilitating excellent autoadsorption/desorption of the spilled oil. The photothermal bactericidal activity and fouling resistance of the foam are beneficial to the separation of bacteria-containing oily wastewater. Outstanding flame-retardant properties and maneuverable magnetic control enable the foam to rapidly recover the spilled oil in a large range of fires, extinguish fires instantly, and facilitate early fire warning. The proposed strategy is expected to inspire further research on treating oil spills under complex conditions. Graphical abstract: : Image, graphical abstract